2003
DOI: 10.1099/vir.0.19320-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the 37 kDa protein of Soil-borne wheat mosaic virus is a virus movement protein

Abstract: Experiments were conducted to determine if the 37 kDa protein (37K) of Soil-borne wheat mosaic virus (SBWMV) is a virus movement protein. First, evidence was obtained that indicated that 37K has the ability to move from cell to cell, similar to other virus movement proteins (MPs). Plasmids containing the GFP gene fused to the SBWMV 37K, the coat protein (CP) or the CP readthrough domain (RT) ORFs were delivered by biolistic bombardment to wheat and tobacco leaves. In wheat leaves, cell-to-cell movement of GFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…The pattern of NSvc4 accumulation is similar to that observed previously for TMV and Cucumber mosaic virus MPs and for the Soilborne wheat mosaic virus 37K protein (1,12,13,29,40). Our observation of NSvc4 in cell walls though immunocytochemistry suggests that RSV NSvc4 may interact with the cytoskeleton and/or ER network in RSV-infected rice cells and travel along the network from viral replication sites to PDs in walls.…”
Section: Discussionsupporting
confidence: 67%
“…The pattern of NSvc4 accumulation is similar to that observed previously for TMV and Cucumber mosaic virus MPs and for the Soilborne wheat mosaic virus 37K protein (1,12,13,29,40). Our observation of NSvc4 in cell walls though immunocytochemistry suggests that RSV NSvc4 may interact with the cytoskeleton and/or ER network in RSV-infected rice cells and travel along the network from viral replication sites to PDs in walls.…”
Section: Discussionsupporting
confidence: 67%
“…Soil-borne wheat mosaic virus (SBWMV), a positive-strand plant RNA virus, has a bipartite genome consisting of two RNA molecules, RNA1 and RNA2 (27,28). RNA1 encodes replication proteins and a movement protein (MP) for cell-to-cell movement (2). RNA2 encodes the capsid protein (CP) and two CP-containing proteins: CP-RT, produced by readthrough of a stop codon, and N-CP, initiated from an upstream CUG codon (25).…”
Section: Resultsmentioning
confidence: 99%
“…Then, substituting 0.5 for r 0 , we simultaneously estimated 0 , 1 , and 2 by maximizing the total log likelihood logL ϭ logL 0 ϩ logL 1 ϩ logL 2 Calculation was done using statistical computing software R (22), and we obtained the mean bottleneck sizes 0 ϭ 5.59 Ϯ 0.40, 1 ϭ 5.97 Ϯ 0.22, and 2 ϭ 5.02 Ϯ 0.29 (maximum likelihood estimates Ϯ standard errors).…”
Section: Resultsmentioning
confidence: 99%
“…The 30K superfamily of viral movement proteins has been demonstrated to have a variety of activities, including the ability to bind nucleic acids, to move to neighboring cells after microinjection or biolistic bombardment, to facilitate movement of RNA to neighboring cells, and to form tubular structures. Although the 30K MPs have similar functions, they exhibit very limited conservation of amino acid sequence (2,25). Instead, it has been suggested that a common three-dimensional structure built of a series of similarly organized secondary structure elements forms the basis for recognition of the putative 30K superfamily members (25).…”
mentioning
confidence: 99%